2015
DOI: 10.1111/anu.12344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth performance and intestinal barrier function in Arctic Charr (Salvelinus alpinus) fed yeast (Saccharomyces cerevisiae), fungi (Rhizopus oryzae) and blue mussel (Mytilus edulis)

Abstract: Arctic charr (Salvelinus alpinus) were fed for 99 days on experimental diets with 40% of fish meal replaced, on a crude protein basis, with intact yeast (Saccharomyces cerevisiae) (ISC), extracted yeast (ESC), Rhizopus oryzae fungus (RHO) or de-shelled blue mussels (Mytilus edulis) (MYE). The fish were evaluated for growth performance, nutrient digestibility and fish intestinal function. Growth performance, retention of crude protein and sum of amino acids were not affected in fish fed diets ISC or MYE compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 55 publications
3
60
1
1
Order By: Relevance
“…; Vidaković et al . ), and thus increased digestibility at warmer temperature may have a larger effect on salmonids fed yeast. These results indicate that feeding live yeast in warm rather than cold water, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Vidaković et al . ), and thus increased digestibility at warmer temperature may have a larger effect on salmonids fed yeast. These results indicate that feeding live yeast in warm rather than cold water, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…), Arctic charr ( Salvelinus alpinus ) (Vidaković et al . ) and lake trout ( Salvelinus namaycush ) (Rumsey et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it seems likely that the whole yeast biomass, after rupturing of cell walls, may be the most attractive feed ingredient, by combining the properties as a source of nutrients and bioactive components. Extrusion of feed may cause partial disruption of yeast cell walls and potentially increase protein and amino acid digestibility . Further research is warranted to determine optimal extrusion conditions for fish feed with contents of different yeast whole cell products.…”
Section: Digestibility Of Yeast In Fishmentioning
confidence: 99%
“…As an easily available natural industrial product, strains of S. cerevisiae have been used as a protein source in a number of studies with different fish species. Several growth performance studies have shown that intact S. cerevisiae can be used to partly replace fishmeal protein in diets for fish species such as sea bass; the omnivore pacu, Piaractus mesopotamicus ; Nile tilapia, Oreochromis niloticus ; Atlantic salmon; Thai Panga, Pangasianodon hypophthalmus × Pangasius bocourti ; and Arctic char . A majority of these studies have been carried out with isonitrogenous and isoenergetic diets, with or without balancing amino acid composition with synthetic amino acids.…”
Section: Effect Of Dietary Yeast On Growth Performance Nitrogen Utilmentioning
confidence: 99%
“…Selain makanan untuk manusia, Rhizopus sp. juga dikembangkan sebagai makanan hewan atau pakan, baik sebagai agen fermentasi untuk memperbaiki kualitas nutrisi bahan pakan (Umam et al 2015;Kurniati et al 2017;Valdez-González et al 2017), maupun sebagai biomassa atau komponen bahan pakan kaya nutrisi, khususnya protein (Ferreira et al 2013;Abro et al 2014a;Abro et al 2014b;Langeland et al 2016;Satari et al 2016;Vidakovic et al 2016;FazeliNejad et al 2016;Souza Filho et al 2017).…”
Section: Pendahuluanunclassified